2023
DOI: 10.1002/jmri.28880
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Stroke Outcomes in Conservatively Treated Patients With Moyamoya Disease: A Follow‐up MRI Study

Abstract: BackgroundLittle is known about the association between stroke and imaging and clinical features in conservatively treated patients with moyamoya disease (MMD).PurposeTo investigate independent risk factors for stroke in conservatively treated patients with MMD during a long‐term follow‐up.Study TypeProspective study.SubjectsOne hundred sixty conservatively managed patients with MMD (median age 46 years, 89 male).Field Strength/SequenceTime of flight, turbo inversion recovery magnitude T1WI, turbo spin echo (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It can be seen that PCES can help detect major blood vessels that cause bleeding in MMD patients ( Ryu et al, 2022 ). Using HR-VWI to predict stroke incidence in conservatively treated MMD patients, one prospective study concluded that VWE was significantly associated with an increased incidence of stroke (HR, 4.16; 95% CI, 1.55–11.15) ( Zhang H. et al, 2023 ). However, the small number of subjects in most studies may have biased the final results.…”
Section: Application Of Hr-vwi In MMDmentioning
confidence: 99%
“…It can be seen that PCES can help detect major blood vessels that cause bleeding in MMD patients ( Ryu et al, 2022 ). Using HR-VWI to predict stroke incidence in conservatively treated MMD patients, one prospective study concluded that VWE was significantly associated with an increased incidence of stroke (HR, 4.16; 95% CI, 1.55–11.15) ( Zhang H. et al, 2023 ). However, the small number of subjects in most studies may have biased the final results.…”
Section: Application Of Hr-vwi In MMDmentioning
confidence: 99%